Specialized knowledge and its communication in auditing* - DANOS, PAUL; EICHENSEHER, JOHN W.; HOLT, DORIS L. (Contemporary Accounting Research, 1989)
Abstract. The purpose of this paper is to describe certain aspects of specialized knowledge communication in auditing. The paper discusses the possible organizational responses an audit firm could make when competitive markets require efficient knowledge sharing among auditors and when economies of scale opportunities through division of responsibilities exist. Experienced auditors were surveyed about their consultation with others in their firms for specific types of clients and for different phases of audit engagements. In general, the results suggest limits to expertise‐related economies of scale in the audit setting studied. The required specialized knowledge seems to be close at hand and accessible in most engagements with little need to consult with nonlocal specialists. When consulted, however, the nonlocal specialists are believed to convey important information. Résumé. Les auteurs ont pour but de décrire certains aspects de la communication de connaissances spécialisées en vérification. Ils traitent des différentes réponses organisation‐nelles que peut donner un cabinet de vérification aux exigences des marchés concurrentiels relatives au partage efficient des connaissances chez les vérificateurs et à la possibilité de réaliser des économies d'échelle grâce au partage des responsabilités. Les auteurs ont interrogé des vérificateurs expérimentés dans le but de déterminer s'ils consultaient d'autres vérificateurs de leur cabinet au sujet de certains types précis de clients et pour différentes phases des missions de vérification. De façon générale, les résultats obtenus donnent à penser que les économies d'échelle reliées à l'expertise dans les contextes de vérification étudiés sont limitées. Dans la plupart des missions, il semble que les connaissances spécialisées requises soient à portée de la main et facilement accessibles, sans qu'il soit nécessaire de consulter des spécialistes de l'extérieur. On croit cependant que les spécialistes de l'extérieur livrent de l'information importante lorsqu'ils sont consultés.